A Digital Closed-Loop Control System for MEMS Resonant Pressure Sensors Based on a Quadrature Phase-Locked Loop - Zhou, Mengyang; Xia, Wenliang; Lu, Yulan; Xie, Bo; Chen, Jian; Wang, Junbo; Chen, Deyong (IEEE sensors journal, 2024)
This article presents a quadrature phase-locked-loop (QPLL)-based digital system for closed-loop control of micro-electromechanical system (MEMS) resonant sensors. The system estimates the sensing signal of the resonator in the form of in-phase and quadrature-phase components by an optimization algorithm, which extends the frequency tracking range and automatically adjusts the amplitude to ensure the linear vibration of the resonator. According to the simulation results, the system has the advantages of fast response and good tracking accuracy. The system has been implemented on a field-programmable gate array (FPGA) development board and validated on an MEMS resonant pressure sensor working by electrostatic excitation and capacitive detection. Experiments show that the proposed system exhibits high linearity, faster startup response, and better frequency stability compared with the previous automatic gain control (AGC)-based analog circuit. Furthermore, the system is widely applicable to sensors with similar resonant characteristics. It has great potential for resonant sensors that require amplitude detection, such as weakly coupled sensors based on the mode-localized phenomenon or parametric coupled sensors subject to blue-sideband excitation.